Comparative study on the status of mental well-being among regularly meditating and non-meditating health care personnel in Sri Lanka - Wasantha Gunathunga; Oshadi Jayakody; Larrissa Bartlett; Ishanka Munugoda; Champa Kumudini Gunathunga (College of Community Physicians of Sri Lanka, 2019)
Abstract Background and objectives Meditation holds potential for reducing occupation related stress. However, the current evidence base is largely limited to studies from the western countries with insufficient assessment of performance outcomes. The aim of this study was to examine the differences in the levels of mental well-being and depression between regularly meditating and non-meditating health care personnel from a primarily Buddhist population. Methods This study was a descriptive comparative study designed to determine the status of mental well-being and depression among health care workers (n=60), exploring the moderating effect of having participated in a structured Vipassana informed mindfulness mediation programme. Data was collected six months from the first training session. Mental well-being and depression were assessed using Primary Mental Health Questionnaire (PMHQ) and Centre for Epidemiological Studies- Depression scale (CES-D) respectively. Independent sample T- Test and Wilcoxon Rank Sum Test were performed to determine the differences in 1) the status of metal well- being and 2) the level of depression between regular meditators and non-meditators. Results Regular meditators showed higher levels of mental well-being compared to non-meditators, indicated by a significant difference in PMHQ values (p=0.001) and significantly lower depression levels according to the CES-D scores (p<0.01). Conclusion Our findings suggest that Vipassana informed mindfulness mediation may have profound practical implications in improving mental well-being among health care professionals. This method with its simple and low-cost approach needs to be tested in other professional groups, to increase the generalizability and applicability.